Characterization of SARS‐CoV‐2 humoral immune response in a subject with unique sampling: A case report - Walker, Melanie R.; Idorn, Manja; Bennett, Anja; Søgaard, Max; Salanti, Ali; Ditlev, Sisse B.; Barfod, Lea (Immunity, Inflammation and Disease, 2023)
Background The development of vaccine candidates for COVID‐19, and the administration of booster vaccines, has meant a significant reduction in COVID‐19 related deaths world‐wide and the easing of global restrictions. However, new variants of SARS‐CoV‐2 have emerged with less susceptibility to vaccine induced immunity leading to breakthrough infections among vaccinated people. It is generally acknowledged that immunoglobulins play the major role in immune‐protection, primarily through binding to the SARS‐COV‐2 receptor binding domain (RBD) and thereby inhibiting viral binding to the ACE2 receptor. However, there are limited investigations of anti‐RBD isotypes (IgM, IgG, IgA) and IgG subclasses (IgG1–4) over the course of vaccination and breakthrough infection. Method In this study, SARS‐CoV‐2 humoral immunity is examined in a single subject with unique longitudinal sampling. Over a two year period, the subject received three doses of vaccine, had two active breakthrough infections and 22 blood samples collected. Serological testing included anti‐nucleocapsid total antibodies, anti‐RBD total antibodies, IgG, IgA, IgM and IgG subclasses, neutralization and ACE2 inhibition against the wildtype (WT), Delta and Omicron variants. Results Vaccination and breakthrough infections induced IgG, specifically IgG1 and IgG4 as well as IgM and IgA. IgG1 and IgG4 responses were cross reactive and associated with broad inhibition. Conclusion The findings here provide novel insights into humoral immune response characteristics associated with SARS‐CoV‐2 breakthrough infections. In a Danish subject with unique longitudinal sampling, SARS‐CoV‐2 humoral immunity over a 2‐year period throughout three doses of vaccine and two breakthrough infections is examined. A total of 22 samples are tested for antinucleocapsid total antibodies, anti‐RBD total antibodies, IgG, IgA, IgM, and IgG subclasses, neutralization and ACE2 inhibition against the wildtype (WT), Delta and Omicron variants. We find that vaccination and breakthrough infection induce cross‐reactive inhibitory IgG1 and IgG4 antibodies, highlighting the need to characterize these responses, as future vaccine design efforts may seek to promote such anti‐RBD IgG1 and IgG4 responses.